2013
DOI: 10.1021/jf4021812
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional 31P,1H NMR Spectroscopic Profiling of Phospholipids in Cheese and Fish

Abstract: Phospholipids (PLs) comprise an important lipid class in food because of their technological use as emulsifiers and their nutritional value. This study used one-dimensional (31)P NMR and two-dimensional (2D) (31)P,(1)H COSY NMR spectroscopy for the determination of the PL composition of cheese and fish after liquid-liquid enrichment. This extraction step enabled the identification of 10 PLs in cheese and 9 PLs in fish by 2D (31)P,(1)H NMR. Variations in the (31)P shifts indicated differences in the fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Phospholipids, such as PE and PC, have been identified in various dairy products (Contarini and Povolo 2013;Kaffarnik et al 2013). The TLC polar lipid fractions of the cheese samples of the present study, which exhibited potent biological activity, were found to have similar R f values to those of SM, PC and PE.…”
Section: Discussionsupporting
confidence: 54%
“…Phospholipids, such as PE and PC, have been identified in various dairy products (Contarini and Povolo 2013;Kaffarnik et al 2013). The TLC polar lipid fractions of the cheese samples of the present study, which exhibited potent biological activity, were found to have similar R f values to those of SM, PC and PE.…”
Section: Discussionsupporting
confidence: 54%
“…NMR has the ability to serve as an invaluable tool for the compositional analysis of foods, not only due to its ability to provide important information for structural elucidation, but also for its quantitative nature. NMR has been effectively used for the analysis of several classes of compounds including lipids (Dais & Hatzakis, ; Monakhova & Diehl, , ; Siddiqui et al., ; Tsiafoulis et al., ), carbohydrates (Kazalaki et al., ; Merkx, Hong, Ermacora, & van, ; Singh, Kumar, Srivastava, Deepak, & Singh, ; Spraul et al., , ), amino acids (Belton et al., ), alcohols (Hatzakis, Archavlis, & Dais, ; Nilsson et al., ), organic acids (Berregi, del Campo, Caracena, & Miranda, ), polyphenols (Agiomyrgianaki & Dais, , ; Charisiadis, Exarchou, Troganis, & Gerothanassis, ), vitamins (Ackermann et al., ; Dais et al., ; Shumilina, Ciampa, Capozzi, Rustad, & Dikiy, ; Vaysse et al., ), terpenes (Dais, Plessel, Williamson, & Hatzakis, ), phospholipids (Hatzakis, Koidis, Boskou, & Dais, ; Kaffarnik, Ehlers, Gröbner, Schleucher, & Vetter, ), colorants (Englert, ; Scotter, ; Venkatachalam et al., ; Berké, Chèze, Vercauteren, & Deffieux, ), and contaminants (Lachenmeier et al., ) in a variety of foods, such as oils (Dais & Hatzakis, ; Siddiqui et al., ), beverages (Kidrič, ; Ryu, Koda, Miyaka, & Tanokura, ; Santos, Fonseca, Lião, Alcantara, & Barison, ; Zurriarrain et al., 2015), meats (García‐García et al., ), dairy products (Gangwar, Singh, & Deepak, ; Hu, Furihata, Ito‐Ishida, Kaminogawa, & Tanokura, ; Maher & Rochfort, ; Murgia, Mele, & Monduzzi, ; Scano et al., ; Tociu et al., ), and infant formula (Zhao et al., ). For the structural characterization of various food components, the application of 2D techniques is often required.…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…Total PL content plus PL profiles were determined using phosphorous nuclear magnetic resonance ( 31 P NMR). This technique is being increasingly used on its own, or in conjunction with hydrogen nuclear magnetic resonance ( 1 H NMR) and carbon nuclear magnetic resonance ( 31 C NMR), for both qualitative and quantitative analyses of PL in diverse biological matrixes, including fish oil (Kaffarnik, Ehlers, Gröbner, Schleucher, & Vetter, 2013;Li, Yang, Bai, & Liu, 2013;Siddiqui et al, 2003;Williamson & Hatzakis, 2017).…”
Section: Introductionmentioning
confidence: 99%